-6=16-2(7+c)

Simple and best practice solution for -6=16-2(7+c) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=16-2(7+c) equation:



-6=16-2(7+c)
We move all terms to the left:
-6-(16-2(7+c))=0
We add all the numbers together, and all the variables
-(16-2(c+7))-6=0
We calculate terms in parentheses: -(16-2(c+7)), so:
16-2(c+7)
determiningTheFunctionDomain -2(c+7)+16
We multiply parentheses
-2c-14+16
We add all the numbers together, and all the variables
-2c+2
Back to the equation:
-(-2c+2)
We get rid of parentheses
2c-2-6=0
We add all the numbers together, and all the variables
2c-8=0
We move all terms containing c to the left, all other terms to the right
2c=8
c=8/2
c=4

See similar equations:

| 56=7(b)3 | | -(5y-6)+y=2(8-2y) | | 5(2x-4)=3(3x-6)+x-2=- | | -18=7b-b | | 2(x+4)+3=2x+6= | | (x–5)(x+3)=0 | | 19=x+29 | | 12x+11=29 | | 4x+17=23x= | | 4d-20-6=16-2d-d | | -7=-2(t+8)-13 | | 6f-9=-2f+1 | | -30+9h=51 | | 62+(y+3)=180 | | 3(5x+4)–8x=7x–12 | | 25=8+9(x+3)= | | 8+y/3=16 | | 10x-10=3x+3 | | 7v−5=–5+7v | | 2d-10d=8 | | 3(y–6)=4y–18–y | | -50=10(h+76) | | 4(w+2)=44 | | 3x+5+2x+10+90=180 | | 1+u/2=7 | | 2/3a-1/6=1/4 | | 4x+25+2x+45=3x-15 | | 7w-5=3w+-15 | | -3x-6+8x+4=130 | | (n/2)+(-3)=5 | | 3x+5+2(2x+10)=180 | | r/3+24=73 |

Equations solver categories